Pre-injection of Zebrafish (Danio rerio) tnfb Polyclonal Antibody Decreases the Mortality of Vibrio vulnificus Infected Zebrafish - Li, Suyi; Jiang, Cong; Chen, Hua; Zhang, Lijuan; Ke, Ling; Chen, Xu; Lin, Chentao (Frontiers in Veterinary Science, 2021)
Tumor necrosis factor (TNF) plays an important role in an inflammatory cytokine storm. Over-secretion of TNF by the host in response to infection aggravates the disease. TNF expression level is positively correlated with the mortality caused by some bacterial infections. Therefore, using TNF antibody may alleviate the inflammation to resist bacterial infections. The function of fish TNF-b antibody in bacterial infection is still unclear. In this study, infection models of Vibrio vulnificus FJ03-X2 strain with high pathogenicity and strong virulence were established in zebrafish (Danio rerio) fibroblast cell line (ZF4 cells) and zebrafish. Zebrafish tnfb (Zetnf-b) gene was cloned and expressed by Escherichia coli BL21 (DE3), and Zetnf-b polyclonal antibody was prepared. Pre-injection of Zetnf-b polyclonal antibody and AG-126 before infecting with V. vulnificus could increase the survival rate of zebrafish by 36.6% and 46.7%, respectively. Pre-injection of Zetnf-b polyclonal antibody could effectively decrease the mortality of zebrafish infected by V. vulnificus. Thus, TNF polyclonal antibody therapy could be considered as an effective strategy to control V. vulnificus in fish.